Choosing between GLP-1 Receptor Agonists and DPP-4 Inhibitors: A Pharmacological Perspective. (18th October 2012) - Brown, Dominique Xavier; Evans, Marc
Abstract : In recent years the incretin therapies have provided a new treatment option for patients with type 2 diabetes mellitus (T2DM). The incretin therapies focus on the increasing levels of the two incretin hormones, glucagon-like peptide 1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP). This results in increased glucose dependent insulin synthesis and release. GLP-1 receptor agonists such as liraglutide and exenatide exert an intrinsic biological effect on GLP-1 receptors directly stimulating the release of insulin from pancreatic beta cells. DPP-4 inhibitors such as sitagliptin and linagliptin prevent the inactivation of endogenous GLP-1 and GIP through competitive inhibition of the DPP-4 enzyme. Both incretin therapies have good safety and tolerability profiles and interact minimally with a number of medications commonly prescribed in T2DM. This paper focuses on the pharmacological basis by which the incretin therapies function and how this knowledge can inform and benefit clinical decisions. Each individual incretin agent has benefits and pitfalls relating to aspects such as glycaemic and nonglycaemic efficacy, safety and tolerability, ease of administration, and cost. Overall, a personalized medicine approach has been found to be favourable, tailoring the incretin agent to benefit and suit patient's needs such as renal impairment (RI) or hepatic impairment (HI).